Current situation of neuropathology in Central America - Delgado, Mónica Núñez (Frontiers in Oncology, 2024)
The present situation of neuropathology practice in the Central American region has not been addressed in the past. These are low middle-income countries, and therefore, many do not have a basic immunohistochemistry panel. Cytogenetics and molecular studies are not available in most of Central America. Pediatric brain tumors are diagnosed either by anatomical pathologists or by pediatric pathologists. Access to a weakly Latin American Tumor Board is available to consult cases, but most countries do not participate in these expert meetings. The most recent World Health Organization brain tumor book has a very broad molecular classification of pediatric brain tumors. All these factors make it very difficult to properly diagnose pediatric brain tumors in the region, and this impacts the treatment and overall survival of children with brain tumors.